2021
DOI: 10.1177/00368504211035597
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of simple sequence repeats and development of polymorphic SSR markers in swamp eel (Monopterus albus)

Abstract: Objectives: Swamp eel is one model species for sexual reversion and an aquaculture fish in China. One local strain with deep yellow and big spots of Monopterus albus has been selected for consecutive selective breeding. The objectives of this study were characterizing the Simple Sequence Repeats (SSRs) of M. albus in the assembled genome obtained recently, and developing polymorphic SSRs for future breeding programs. Methods: The genome wide SSRs were mined by using MISA software, and their types and genomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The choice of simple sequence repeats (SSRs) as genetic markers in this genome survey was made after a review of the relevant literature. SSRs have been used as genetic tools in fish and aquaculture for linkage map construction [ 30 ], assessment of genetic diversity [ 31 ], parentage determination [ 32 ], and a genome-wide association study [ 33 ]. The information on SSRs in R. brachysoma and R. kanagurta could be benefit further studies of genetic markers in mackerels.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of simple sequence repeats (SSRs) as genetic markers in this genome survey was made after a review of the relevant literature. SSRs have been used as genetic tools in fish and aquaculture for linkage map construction [ 30 ], assessment of genetic diversity [ 31 ], parentage determination [ 32 ], and a genome-wide association study [ 33 ]. The information on SSRs in R. brachysoma and R. kanagurta could be benefit further studies of genetic markers in mackerels.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of 412,381 SSRs were identified and accounted for 1.24% of the reference genome length. The genome-wide SSR content was similar to that of Takifugu rubripes (0.77%), Takifugu flavidus (0.73%) [ 28 ], and Monopterus albus (1.03%) [ 29 ]. Among different types of repeats, A/T motifs were considerably more common than G/C motifs (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 97%
“…The frequency of SSRs in H. molitrix was 437.73 loci/Mb, lower than that in Cyprinus carpio (621.95 loci/Mb), Oncorhynchus kisutch (461.35 loci/Mb), and Cynoglossus semilaevis (3445.94 loci/Mb) [ 30 ], and higher than that in some birds (80.9–256.9 loci/Mb) [ 26 ] and Lateolabrax maculatus (425.06 loci/Mb) [ 31 ]. The density (7713.16 bp/Mb) was higher than that of Ctenopharyngodon idella (1425.35 bp/Mb) [ 32 ] and lower than that of Monopterus albus (10,259 bp/Mb) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%